"He Was the Story of My Drug Use Life": A Longitudinal Qualitative Study of the Impact of Partner Incarceration on Substance Misuse Patterns Among African American Women. (1st January 2014) - Cooper, Hannah LF; Clark, Claire Ducharme; Barham, Terrika; Embry, Venita; Caruso, Bethany; Comfort, Megan
Abstract : This NIH-funded longitudinal qualitative study explored pathways through which partner incarceration affected substance misuse among African American women. Four waves of semi-structured interviews were conducted with 17 substance-misusing African American women whose partners had recently been incarcerated. Data were collected in Atlanta, Georgia, during 2010–2011. Transcripts were analyzed using grounded theory methods. Analyses suggest that partner incarceration initially precipitated multiple crises in women's lives (e.g., homelessness); over time, and with formal and informal support, women got their lives "back on track." Substance misuse declined over time, though spiked for some women during the crisis period. We discuss implications for research and interventions.